2019
DOI: 10.1371/journal.pone.0212049
|View full text |Cite
|
Sign up to set email alerts
|

The impact of supplementary immunization activities on routine vaccination coverage: An instrumental variable analysis in five low-income countries

Abstract: Background Countries deliver vaccines either through routine health services or supplementary immunization activities (SIAs), usually community-based or door-to-door immunization campaigns. While SIAs have been successful at increasing coverage of vaccines in low- and middle-income countries, they may disrupt the delivery of routine health services. We examine the impact of SIAs on routine vaccine coverage in five low-income countries. Methods Data on the number and tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
11
0
2
Order By: Relevance
“…Limiting their focus on children aged 4 months, the authors argue that one-time exposure to the SIA (comparing children born before and after the campaign) significantly increased uptake of the diphtheria, pertussis and tetanus vaccine (DPT) vaccine as well as routine childhood immunisation more broadly. A related study by Chakrabarti et al 18 expanded the analysis to the broader target group of children under 5 years of age. Using the time when a child was first exposed to one SIA as an instrumental variable for total SIA exposure, the authors found an overall negative relationship between SIA and RI, which was statistically significant in three out of five countries for the period 1992–2013.…”
Section: Methodsmentioning
confidence: 99%
“…Limiting their focus on children aged 4 months, the authors argue that one-time exposure to the SIA (comparing children born before and after the campaign) significantly increased uptake of the diphtheria, pertussis and tetanus vaccine (DPT) vaccine as well as routine childhood immunisation more broadly. A related study by Chakrabarti et al 18 expanded the analysis to the broader target group of children under 5 years of age. Using the time when a child was first exposed to one SIA as an instrumental variable for total SIA exposure, the authors found an overall negative relationship between SIA and RI, which was statistically significant in three out of five countries for the period 1992–2013.…”
Section: Methodsmentioning
confidence: 99%
“…The labour-intensive nature of SIAs and their capacity to monopolise resources can lead to lapses in routine vaccination, following the completion of the campaign. 10 In addition, as vaccine efficacy drops for children vaccinated at <9 months due to possible interference with maternal antibodies, 11 children vaccinated before their optimal age still require two routine doses, 4 6 presenting a serious challenge among transient populations. In addition, a shorter time interval between MCV1 and MCV2 could substantially reduce attrition 6 : we urgently need further research into the long-term protective effects of administering MCV2 as early as 28 days after MCV1 (the minimum interval between two live vaccines), rather than the prescribed 15–18 months of age.…”
Section: Supplementary Immunization Activities: a Double-edged Swordmentioning
confidence: 99%
“…Since maternal and neonatal tetanus occurs more in communities where there is high prevalence of unclean home deliveries practiced by traditional birth attendants, the two immunization approaches are likely to have greatest impact in the low-resource regions of the world. While supplementary immunization have been successful in increasing the coverage of vaccines in low-resource regions, particularly in conflict zones such as in Afghanistan and Somalia, these activities have recently been found to be unintentionally detrimental and disruptive to the routine health services (34). The authors have called for greater support for routine services to complement supplementary health services.…”
Section: Immunizationmentioning
confidence: 99%